Handbook of electric tables and design criteria - Christoffer, V. F. (McGraw-Hill, 1998)
The book features tables and data for aluminum and cooper conductors; calculation forms for voltage drop and derating of conductors; circuit design data for three-phase motors and transformers; data for power factor correction; NEMA ratings for enclosures; fault-current tables, data, and calculation forms.